2010
DOI: 10.1590/s0066-782x2010005000146
|View full text |Cite
|
Sign up to set email alerts
|

Estudo de fatores pró-trombóticos e pró-inflamatórios na cardiomiopatia chagásica

Abstract: There is no evidence of greater pro-thrombotic status among patients with Chagas disease. The levels of fibrinogen and the MA, G and TG parameters of the thromboelastography point to pro-thrombotic status among non-chagas patients. Both groups had increased inflammatory activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Our results concerning progressive heart failure death are in concordance with other previous publications that included chagasic patients also under outdated treatment [17], [18]. Our finding of high incidence of stroke causing death in Chagas disease in comparison with other etiologies confirms previous studies [18], [19] despite the unexpected recently reported lack of evidence of pro-thrombotic status among patients with Chagas disease [20]. However, cardiac embolus originating from apical aneurysm and left ventricular thrombosis are a recurrent cause of Chagas stroke [21].…”
Section: Discussionsupporting
confidence: 92%
“…Our results concerning progressive heart failure death are in concordance with other previous publications that included chagasic patients also under outdated treatment [17], [18]. Our finding of high incidence of stroke causing death in Chagas disease in comparison with other etiologies confirms previous studies [18], [19] despite the unexpected recently reported lack of evidence of pro-thrombotic status among patients with Chagas disease [20]. However, cardiac embolus originating from apical aneurysm and left ventricular thrombosis are a recurrent cause of Chagas stroke [21].…”
Section: Discussionsupporting
confidence: 92%
“…Another important point to be considered is the absolute hegemony of studies carried out in Brazil (77% of those included in this review) 4,6-9,11,12,14-19,21-26,28-36,38,40-43 . Among the five studies performed in other countries, three were carried out in Latin America 13,20,27 and two in Europe 37,39 .…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the use of comparison groups, it was observed that in 18 articles (58%) the authors used the design of comparisons between groups 8,13-18,21,24,26,27,31,35,37,33,40-41,43 . It is also interesting to note the predominance of adult patients in the selected studies, with only one study including adolescent chagasic patients 23 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations